Anne Hébert et l’univers de la radio - Ferraro, Alessandra (Ponti/Ponts, 2021)
The different versions of L’Île de la Demoiselle and the notes of realization of this radio play by George Godebert, (broadcast France-Culture, 1978), are put in relation with the previously little known radio production of the Quebecer author. We show that the choice of the radio drama, which relies only on dialogues or sounds, responds to Anne Hébert’s desire to give voice to historical female characters who haunt her imagination. This approach also makes it possible to make some hypotheses on the genesis of the cycle of works devoted to New France which also includes La Cage and Le premier jardin.